On the use of antibiotics to control plant pathogenic bacteria: a genetic and genomic perspective - Verhaegen, Marie; Bergot, Thomas; Liebana, Ernesto; Stancanelli, Giuseppe; Streissl, Franz; Mingeot-Leclercq, Marie-Paule; Mahillon, Jacques; Bragard, Claude (Frontiers in Microbiology, 2023)
Despite growing attention, antibiotics (such as streptomycin, oxytetracycline or kasugamycin) are still used worldwide for the control of major bacterial plant diseases. This raises concerns on their potential, yet unknown impact on antibiotic and multidrug resistances and the spread of their genetic determinants among bacterial pathogens. Antibiotic resistance genes (ARGs) have been identified in plant pathogenic bacteria (PPB), with streptomycin resistance genes being the most commonly reported. Therefore, the contribution of mobile genetic elements (MGEs) to their spread among PPB, as well as their ability to transfer to other bacteria, need to be further explored. The only well-documented example of ARGs vector in PPB, Tn5393 and its highly similar variants (carrying streptomycin resistance genes), is concerning because of its presence outside PPB, in Salmonella enterica and Klebsiella pneumoniae, two major human pathogens. Although its structure among PPB is still relatively simple, in human- and animal-associated bacteria, Tn5393 has evolved into complex associations with other MGEs and ARGs. This review sheds light on ARGs and MGEs associated with PPB, but also investigates the potential role of antibiotic use in resistance selection in plant-associated bacteria.